Investigating Teacher Agency: Zoning Policy Implementation in Favorite and Non-Favorite Senior High Schools - Wardani, Dyah Ayu Kusuma (Universitas Negeri Semarang, 2020)
Teacher agency plays a significant role in successful teaching. Upon the implementation of student enrollment zoning policy throughout the country (since 2018), demographic changes started to occur. Favorite schools in the city of Yogyakarta inevitably had to admit students with less academic skills, making teaching activities more complex and difficult among teachers. This study attempts to reveal how English teachers dealt with such dynamic changes. This study employed qualitative method. Twelve English teachers from favorite and non-favorite senior high schools in Yogyakarta, Bantul and Sleman were involved in this study. They were purposively selected for semi-structured interviews and two of them were invited to have in-depth interviews. The results showed that those two English teachers were agentic. The zoning policy was largely seen to have created unnecessary challenges among English teachers. During the pre-zoning policy, students were homogeneous in terms of background knowledge and academic skills. Such a homogeneity ended after the policy was implemented. However, interview data gathered in this study strongly suggest that teachers were able to navigate themselves, mostly due to warm, academic culture of their school. The warm school culture has successfully bridged the diversity of students’ abilities in the class.